2015
DOI: 10.6000/1927-5129.2015.11.73
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sowing Dates on Growth, Yield and Grain Quality of Hybrid Maize

Abstract: The experiment was laid out in Randomized Complete Block Design (factorial) with three replications having net plot size 3x4m=(12m 2). The effect of three sowing dates 25 th October, 10 th November and 25 th November on three hybrid maize varieties Pioneer 1543, Syngenta 4841 and Monsanto DK-6142 was studied. Yield components and grain quality parameters such as plant height, number of cobs per plant, cob length, grains per cob, grain yield, protein, starch and oil content of maize varieties were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 10 publications
7
25
0
Order By: Relevance
“…These results corroborate the findings of Jehangir et al who also found increase in protein content in oats in late sowing compared to early sowing [21]. Although previous research found decrease of grain quality in late sown maize, means for protein content in late sown maize were higher than in early sown maize [20,22].…”
Section: Biochemical Mean Linkage Cluster Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…These results corroborate the findings of Jehangir et al who also found increase in protein content in oats in late sowing compared to early sowing [21]. Although previous research found decrease of grain quality in late sown maize, means for protein content in late sown maize were higher than in early sown maize [20,22].…”
Section: Biochemical Mean Linkage Cluster Analysissupporting
confidence: 90%
“…Early sowing, vis-a-vis late sowing affects grain yield and composition. Early sowing provides longer growing period and efficient grain filing, while late sowing was found to shorten maize cycle leading to low yield and poor quality grain in maize [22]. Currently, limited information is available on the effect of sowing dates on sorghum quality parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical compositions of KW and PI hybrids were in the expected range for corn grown in South Korea [9,10,24,25]. In general, the differences of silage chemical compositions among hybrids are caused by those of forages [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…In South Korea, Kwangpyeongok (KW) and Pioneer 1543 (PI) are the most widely planted corn hybrids in ruminant industry to supply feed forages. The KW hybrid is more adaptive resulting in higher dry matter (DM) yield and resistance to black-streaked dwarf virus [9], while PI hybrid produces higher grain yield [10]. The previous studies reported that application of hybrid had effect on fermentation quality and aerobic stability of corn silage [1113].…”
Section: Introductionmentioning
confidence: 99%
“…Heat stress trends to produce reactive oxygen species such as OH -, H 2 O 2 , and O 2 -that eventually decline the enzymatic activity of chloroplast and mitochondria, and eventually minimize the protein synthesis in plants, tissues and necrosis of cells, and minimize grain yield in cereals i.e. rice, wheat, and maize (Casini, 2012;Buriro et al, 2015).…”
Section: Introductionmentioning
confidence: 99%